Original paperRelationship between Helicobacter pylori and idiopathic chronic urticaria: effectiveness of Helicobacter pylori eradication - Mogaddam, Majid Rostami; Yazdanbod, Abbas; Ardabili, Nastaran Safavi; Maleki, Nasrollah; Isazadeh, Sonia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Chronic urticaria (CU) is defined as the presence of urticaria on most days of the week for a period of 6 weeks or longer. Some studies have reported an association between CU and Helicobacter pylori ( H. pylori ) infection. Aim: To determine the prevalence of H. pylori infection using the stool antigen test in patients with idiopathic CU and to investigate the infected patients with CU following eradication of H. pylori . Material and methods: One hundred patients with idiopathic CU and 100 healthy controls were referred to our clinic between May 2012 and June 2013 and were tested for H. pylori antigen. The patients infected with H. pylori received quadruple therapy for 2 weeks. To assess eradication efficacy, a repeated H. pylori stool antigen test was performed in each patient 6 weeks after the end of anti- H. pylori therapy. The effectiveness of eradication therapy on CU was assessed 3 months after treatment. Results : Thirty-six percent patients with idiopathic CU were infected with H. pylori while 23% of the controls were infected. Response to eradication therapy was evident in 33 (91.67%) patients in whom H. pylori was eradicated while 3 (8.33%) patients showed no response despite eradication of H. pylori . Clinical follow-up of 33 successfully treated patients 3 months later revealed complete remission of urticaria in 54.5%, partial remission in 18.2%, and no improvement in 27.3%. Conclusions : The results of our study suggest that H. pylori infection should be included in diagnostic workup of patients with no response to habitual treatment for CU or symptomatic gastrointestinal patients. For the diagnosis of H. pylori infection, one should consider the costs and accessibility of the population to the HpSA® stool antigen test and Urea breath test (UBT).